Reduction of arenediazonium salts by tetrakis(dimethylamino)ethylene (TDAE): Efficient formation of products derived from aryl radicals - Mahesh, Mohan; Murphy, John A.; LeStrat, Franck; Wessel, Hans Peter (Beilstein Journal of Organic Chemistry, 2009)
Tetrakis(dimethylamino)ethylene (TDAE 1), has been exploited for the first time as a mild reagent for the reduction of arenediazonium salts to aryl radical intermediates through a single electron transfer (SET) pathway. Cyclization of the aryl radicals produced in this way led, in appropriate substrates, to syntheses of indolines and indoles. Cascade radical cyclizations of aryl radicals derived from arenediazonium salts are also reported. The relative ease of removal of the oxidized by-products of TDAE from the reaction mixture makes the methodology synthetically attractive.
Keywords: cyclization; electron transfer; indole; indoline; radical